Developing Community-Appropriate Sleep Apnea Messaging Through Appreciative Inquiry and Boot Camp Translation: A Qualitative Study - Tristen L. Hall; Matthew J. Simpson; Griselda Peña-Jackson; John M. Westfall; Donald E. Nease, Jr (The University of Alabama, 2022)
Undiagnosed sleep apnea is a substantial burden in the United States, leading to negative health impacts and unnecessary costs. Diagnosing sleep apnea is challenging due to a lack of evidence to justify universal screening and discomfort associated with sleep studies. This study used semi-structured, individual interviews (N = 12) to examine how community members with sleep apnea become diagnosed and identify effective strategies to manage their condition. Findings from these interviews, in turn, were used to develop messaging campaigns intended to increase community members' awareness of undetected sleep apnea. Influences from a variety of social and health care-related sources helped participants identify effective treatment strategies. Delays occurred at multiple points in the diagnostic process from symptom recognition through treatment, and finding effective treatment required trial and error. There is room to improve sleep apnea screening and diagnosis efforts in ambulatory care settings to better address high rates of undiagnosed sleep apnea. Community- and clinic-based strategies to incorporate sleep into patient-provider discussions and screen more broadly for sleep disorders could reduce the prevalence and duration of untreated sleep apnea.